Traditional uses, phytochemistry profile and biological properties of Jarum Tujuh Bilah, Pereskia bleo: a review / Nur Azwa Hanim Azizan ... [et al.] - Azizan, Nur Azwa Hanim; Aris, Farizan; Mat Jalil, Mohd Taufiq; Mohamed Yunus, Norfatimah; Ab Rashid, Syarifah; Zakaria, Nurul Aili (Faculty of Applied Sciences, 2024)
Pereskia bleo is a species that belongs to the family of Cactaceae and is distributed across Asia, Southeast Asia, and America. This plant grows in regions receiving high annual rainfall. Featuring their non-succulent green leaves, thorny stems, and occasionally red-orange flowers, they are very popular ornamental shrubs. They are widely used as traditional medicines to prevent cancer and treat diseases such as hypertension, muscle aches, boils, and diabetes. This species has been scantily studied so far. More attention and effort are required to draw a link between these species' traditional uses, active compounds, and pharmacological activities. This manuscript aims to critically analyze the distribution, traditional uses, factors influencing the extraction of bioactive compounds, and phytochemical contents of P. bleo. The numerous biological properties of P. bleo were also presented, including antioxidant, anticancer, anti-diabetic, anti-nociceptive, antimicrobial activities, and larvicidal studies. P. bleo exhibits diverse biological activities that are very useful for medical treatment. The integrated knowledge of P. bleo will support its potential exploration in research of pharmacology and food sectors and sanguinely proffer commercialization opportunities.